Analysis of Sepancong Hill Tourism's Carrying Capacity in the District of Bengkayang - Slamet Rifanjani; Muflihati; Rosalia Meida Astrida; Munadian (Journal of Sylva Indonesiana, 2023)
Sepancong Hill is one of the tourist attractions in Bengkayang Regency. According to the survey, there is an increase in tourist visits from day to day. If it continues, it will lead to environmental problems caused by an excessive number of tourists. This research aimed to get the maximum number of tourists according to the carrying capacity of Sepancong Tourism. The method used in this study is to calculate the Physical Carrying Capacity (PCC), Real Carrying Capacity (RCC), and Effective Carrying Capacity (ECC). The analysis used is descriptive quantitative analysis. Sepancong Hill nature tourism is divided into two areas, such as the campsite and Orchid Park. This research showed that the PCC of both areas is 182 and 356, respectively. The RCC of the campsite and orchid park are 51 and 101. The ECC of the camping area and Orchid Park are 51 and 101. The carrying capacity values for both are obtained by the equation PCC > RCC â‰¥ ECC. The PCC of the whole hill of Sepancong is 352. It means that the carrying capacity of Sepancong Hill is large and can still accommodate tourists with all tourist activities.